What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique

Unmarked: the politics of performance - Phelan, Peggy (Routledge, 1993)
Feminist film theory has made the psychic and political limitations of representational visibility abundantly clear. Yet the Left continues to promote visibility politics as a crucial aspect of progressive struggle. Unmarked examines the fraught relation between political and representational visibility and invisibility within both mainstream and avant-garde art. Suggesting that there may be some political power in an active disappearance from the visual field, Phelan looks carefully at examples of such absences in photography, film, theatre, the iconography of anti-abortion demonstrations, and performance art. A boldly specultative analysis of contemporary culture, Unmarked is a controversial study of the politics of performance. Situating performance theory within emerging theories of psychoanalysis, feminism, and cultural studies, Phelan argues that the non-reproductive power of performance offers a different way of thinking about cultural production and reproduction more generally. Written from and for the Left, Phelan's readings of the work of Robert Mapplethorpe, Cindy Sherman, Mira Schor, Yvonne Rainer, Jennie Livingstone, Tom Stoppard, Angelika Festa and Operation Rescue radically rethink the politics of cultural representation.
Keywords: amériques; approches et analyses; arts; cours; discipline; féminisme pop; har4600; histoire de l'art; histoire et politique; performance; philosophie; premier cycle; psychanalyse; ressource en ligne; régions géographiques; sciences; sciences humaines; sex2283; thématiques; états-unis